BSA-assisted synthesis of ultrasmall gallic acid–Fe(III) coordination polymer nanoparticles for cancer theranostics - Mu X (Dove Medical Press, 2017)
Xueling Mu,1–3 Chenglin Yan,1–3 Qiwei Tian,1–3 Jiaomin Lin,1–3 Shiping Yang1–3 1Key Laboratory of Resource Chemistry, 2Key Laboratory of Rare Earth Functional Materials, 3Key Laboratory of Molecular Imaging Probes and Sensors, Shanghai Normal University, Shanghai, China Abstract: Protein-related nanotheranostic agents hold great promise as tools to serve many clinical applications. Proteins such as BSA are used to regulate the synthesis of nondegradable inorganic nanoparticles (NPs). To fully employ the potential of such proteins, a new type of biosafe nanotheranostic agent must be designed to optimize BSA as a biomineralization agent. Here, a straightforward BSA-assisted biomineralization method was developed to prepare gallic acid (GA)–Fe(III) coordination polymer NPs. BSA-coated GA-Fe (GA-Fe@BSA) NPs were ultrasmall (3.5 nm) and showed good biocompatibility, a lower r2:r1 ratio (1.06), and strong absorption in the visible near-infrared region. T1-weighted magnetic resonance imaging of tumor-bearing mice before and after intratumoral injection with GA-Fe@BSA NPs definitively demonstrated positive change. In a subsequent in vivo study, antitumor activity was precipitated by intratumoral injection of GA-Fe@BSA NPs combined with laser treatment, suggesting excellent outcomes with this treatment method. These results describe a successful protocol in which BSA regulated the synthesis of benign organic polymer NPs. GA-Fe@BSA NPs have the potential to be ideal agents to be used in clinical theranostic nanoplatforms. Keywords: BSA, MRI, gallic acid, coordination polymer, theranostics